Um olhar linguístico-filosófico para as interações em chatbot - Brum, Bruna Oliveira (2022)
With the objective of analyzing how interactions with bots are constructed in order to understand which conditions favor or hinder the resolution of service users problems, this work presents, initially, an overview of the concept of language and language spoken in the view of theorists from different areas of interest within linguistics, as well as a study on the concepts of verbal interaction, dialogic relation and expressive intonation, presuppositions of the Bakhtin circle. The research also brings an understanding of computational logic, the notion of artificial intelligence development, algorithms and techniques involved in the development of chatbots interaction in order to understand, albeit superficially in technical terms, the processes of creation and programming of bots. In the light of the concepts studied, an analysis of the effectiveness of the interaction in four interactions between clients and bots of companies from different segments is given. From this sample, the research concludes that the condition that favors the interaction between men and bots is the need for both to axiologize the language, that is, the bot must be able to receive the language and to perceive it as a sign materiality. That must be reflected and refracted before being responded to, a capacity intrinsic to man and essential to successful interaction.